계통 연계형 4레그 인버터에서 상 개별 무효전력 제어를 이용한 PCC 전압 안정화 - 이진성; 전정환; 이상준; 이교범 (조명.전기설비학회논문지, 2025)
This paper proposes a reactive power control method in grid-connected four-leg inverter for stabilizing the point of common coupling(PCC) voltage. The proposed method controls the magnitude of the reactive power output from the inverter to ensure that the PCC voltage satisfies the defined standard when the voltage at the PCC point is higher or lower than the reference value. Reactive power outputs are regulated based on the control curve for PCC voltage defined by the Korean Grid Association. A strategy to control each phase individually is required to control the PCC voltage of each phase since the magnitude of the PCC voltage can vary across phases depending on the load applied to each phase. The individual-phase control strategy is employed for the reactive power control to regulate the PCC voltage of each phase in this paper. The PCC voltage of each phase is stabilized through the reactive power control with individual-phase control when the loads on the phases are unbalanced. The validity of the proposed method is demonstrated through simulation results.
Keywords: Distributed energy resources; Four-leg inverter; Grid-connected; PCC; Phase locked loop; Volt-VAR control